On Urban Creativity in Argentina Over Time: The Need for Locally Contextualized Studies - dos Santos, María Laura (Street Art & Urban Creativity, 2020)
Argentinian academic research and production on urban creativity is not recent; the field has developed through a combination of different disciplines and perspectives. But what is remarkable is the shift in interest on the subject since the arrival of the New York Style Graffiti Writing in the late ‘90s, which made new theoretical frameworks for the phenomena possible. Considering all these multiple approaches to the subject matter, the lack of consensus and systematic research is even more noteworthy, as it generates a heterogeneous panorama in terms of research proposals and frameworks. In this article, we will examine the way in which a field of studies on graffiti and urban art emerged in Argentina -retracing the frameworks that structured the understanding of urban creativity through lineages or inheritances-, and we will show a continuation of interest in the subject matter, reshaped as a result of the arrival of new research perspectives.